2018
DOI: 10.1155/2018/6149263
|View full text |Cite
|
Sign up to set email alerts
|

A Strong Graded Relationship between Level of Obesity and COPD: Findings from a National Population-Based Study of Lifelong Nonsmokers

Abstract: Factors associated with chronic obstructive pulmonary disease (COPD) among never-smokers have received little research attention. One potential risk factor for COPD is obesity, which is of particular importance in light of the global obesity epidemic. The objective of this study was to investigate the association between COPD and levels of obesity in a nationally representative sample of non-Hispanic white never-smokers. Data were drawn from the 2012 Center for Disease Control's Behavioral Risk Factor Surveill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
1
12
2
4
Order By: Relevance
“…Excess weight is an established risk factor for several health problems, including type 2 diabetes, cardiovascular diseases (CVD), some cancers, chronic obstructive pulmonary diseases (COPD), and mortality. 11 , 12 , 13 , 14 , 15 In a study including more than 10 million participants from 239 prospective studies, all-cause mortality was minimal for persons with BMI between 20 and 25; however, each 5-unit increase in BMI above 25 was associated with a 49%, 38%, and 19% higher risk of CVD, respiratory disease, and cancer mortality, respectively. 13 Another study based on data from 12 European cohort studies found that each 5-unit increase in BMI was associated with an increase in CVD mortality of 34% in men and 29% in women.…”
Section: Introductionmentioning
confidence: 99%
“…Excess weight is an established risk factor for several health problems, including type 2 diabetes, cardiovascular diseases (CVD), some cancers, chronic obstructive pulmonary diseases (COPD), and mortality. 11 , 12 , 13 , 14 , 15 In a study including more than 10 million participants from 239 prospective studies, all-cause mortality was minimal for persons with BMI between 20 and 25; however, each 5-unit increase in BMI above 25 was associated with a 49%, 38%, and 19% higher risk of CVD, respiratory disease, and cancer mortality, respectively. 13 Another study based on data from 12 European cohort studies found that each 5-unit increase in BMI was associated with an increase in CVD mortality of 34% in men and 29% in women.…”
Section: Introductionmentioning
confidence: 99%
“…82 Beden Kitle İndeksi artışının KOAH, astım ve obstrüktif uyku apnesi riski ile ilişkili olması, obezitenin respiratuar hastalıklardaki anahtar rolünü doğrulamaktadır. [83][84][85] Respiratuar hastalıklar ile obezite arasındaki ilişkide muhtemel mekanizmanın aşırı enerji alımı ile asetil-KoA karboksilaz enzim aktivasyonuna bağlı Th17 farklılaşması ve Th17/Treg oranının artması olduğu düşünülmektedir. 36,37,86 Viral pnömoni ve sekonder bakteriyel enfeksiyonlarının akut akciğer hasarı, ARDS ve nihayetinde ölüme yol açabileceği önceki çalışmalarda belirtilmiştir.…”
Section: Covid-19 İçin Risk Faktörü Olan Respiratuar Hastalıkların Paunclassified
“…In manchen Studien waren Siamkatzen häufiger von Bronchialerkrankungen betroffen als andere Rassen [15] [16] [17]. In der Humanmedizin wurden für beide Krankheitsbilder Rauchen und Adipositas als Risikofaktoren beschrieben [18] [19]. Beim humanen Asthma ließen sich außerdem genetische Faktoren nachweisen [20].…”
Section: Risikofaktorenunclassified